Experimental investigation of thermochemical regeneration using oxy-fuel exhaust gases. (15th February 2019) - Gaber, Christian; Demuth, Martin; Prieler, René; Schluckner, Christoph; Schroettner, Hartmuth; Fitzek, Harald; Hochenauer, Christoph
Highlights: This article investigates the performance of the bi- and tri-reforming of methane. Both bi- and tri-reforming are achievable using oxy-fuel exhaust gases and oxygen. Oxygen has a strong impact on the reforming process, and prevents coke formation. Equilibrium conversions were maintained for 333 h without catalyst deactivation. Water and carbon dioxide were successfully used to regenerate the catalyst. Abstract: Thermochemical regeneration (TCR) improves the efficiency of natural gas-fired oxy-fuel furnaces as the hot exhaust gases are used to reform the primary fuel into syngas. In order to identify optimal process parameters, methane reforming experiments were performed on a small-scale reformer unit using oxy-fuel exhaust gases and oxygen. (I) Stationary bi-reforming experiments with methane, water and carbon dioxide and a steam-to-carbon ratio of 0.5 as well as tri-reforming test runs with additional oxygen and a steam-to-carbon ratio of 0.4 were conducted in order to investigate the long-term stability of the Ni-catalyst. For both the bi- and tri-reforming of methane, the long-term stability of the catalyst is strongly limited by the formation of significant amounts of carbon on the surface of the catalyst. This study also found that tri-reforming with additional oxygen has a significant influence on the amount of carbon formed: Coke-free tri-reforming is possible with an oxygen-to-methane ratio of 0.25 or higher. (II) Apart from a slight dilution of the syngas, the presence of up to 10 vol.% of nitrogen in the fuel/exhaust gas mixture, as could occur due to a furnace leakage, had no significant impact on the performance. (III) The experiments conducted herein demonstrated that both regenerative bi- and tri-reforming showed stable conversion over 90 reforming and regeneration cycles when oxy-fuel exhaust gases were used as regenerative agents, and the cycles were each 15 min long. Regeneration with oxyfuel exhaust gases was able to remove all carbon deposits, produced during the reforming cycles and ensure a semi-stationary TCR operation.